Risk management in banking - Bessis, Joël. (Chichester, United Kingdom : John Wiley, 2010)
This book considers all aspects of risk management emphasizing the need to undersand conceptual and implementation issues of risk management and examining the latest techniques and practical issues, including asset liability management, risk regulations and accounting standards, market risk models, credit risk models etc.
Includes bibliographical references (p. [799]-801) and index.
osa 03/06/13
Loans
Keywords: Bank management; Risk management; Asset-liability management; Banking - risk management